Early detection of pancreatic cancer: A possibility in some cases but not a reality in most - Goh, K.L.; Yoong, B.K. (Wiley, 2012)
Pancreatic cancer is notoriously difficult to diagnose until a late stage when curative options are no longer available. Owing to its relatively low incidence and the lack of sensitivity of current diagnostic tool, screening of pancreatic cancer in the general population is not recommended. However, in high-risk individuals, especially those with well-described genetic syndromes and a strong family history of pancreatic cancer, screening can be carried out. Detection of a lesion of the diameter < 1 cm without lymph node involvements and subsequent removal of the tumor results in long-term cure of the cancer. Endoscopic ultrasound (EUS) is the only diagnostic tool that is able to detect such small lesions. EUS is often combined with endoscopic retrograde cholangiography to augment the diagnostic yield. The conundrum in clinical practice is to differentiate between a malignant and a benign lesion. Resection of the pancreas constitutes major surgery with a high morbidity and mortality. The need continues, therefore, to find even more accurate imaging modalities to diagnose small pancreatic cancers with confidence.